2022
DOI: 10.1039/d1qo01462e
|View full text |Cite
|
Sign up to set email alerts
|

NHC-catalysed [3 + 2]-asymmetric annulation between pyrazolin-4,5-diones and enals: synthesis of novel spirocyclic pyrazolone γ-butyrolactones and computational study of mechanism and stereoselectivity

Abstract: Chiral pyrazolones with a spirocyclic centre at the C4-position are widely found in a large family of medically relevant compounds. In recent years, organocatalysis, particularly that performed with quiral N-heterocyclic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…In the first stage, the NHC catalyst reacts with the aldehyde moiety of β-bromoenal 2, giving rise to the intermediate IM1 which evolves to the Breslow homoenolate IM2 after base-assisted 1,2-hydrogen migration. 12,17 In our previous electronic structure calculations, we proved that the Brønsted base used to generate the carbene catalyst assists the [1,2]-proton transfer for the generation of homoenolate. However, it is also worth mentioning that previous computational studies have found that it is the conjugated acid of the base that leads to the lowest energy barrier.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the first stage, the NHC catalyst reacts with the aldehyde moiety of β-bromoenal 2, giving rise to the intermediate IM1 which evolves to the Breslow homoenolate IM2 after base-assisted 1,2-hydrogen migration. 12,17 In our previous electronic structure calculations, we proved that the Brønsted base used to generate the carbene catalyst assists the [1,2]-proton transfer for the generation of homoenolate. However, it is also worth mentioning that previous computational studies have found that it is the conjugated acid of the base that leads to the lowest energy barrier.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…Very recently, we have described the first asymmetric synthesis of spirocyclic pyrazolone γbutyrolactones by an NHC-catalyzed [3 + 2] annulation reaction. 12 T h i s c o n t e n t i s On the other hand, the γ-butenolide moiety is a motif present in a wide range of natural products and biologically active molecules. In the last few years, several reviews have documented the most recent enantioselective synthetic approaches for the construction of these frameworks, 13 but the development of this field is still in its infancy.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Our group has recently described the first asymmetric synthesis of spirocyclic pyrazolone γ-butyrolactones by an NHC-catalysed [3 + 2] annulation reaction between pyrazolin-4,5-diones and enals. 9 Chiral oxazolidines constitute important structural motifs that are present in many biologically active natural products and pharmaceuticals. 10 Despite the interest in oxazolidines, the organocatalytic asymmetric synthesis of oxazolidines has been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the preparation and functionalization of pyrazolone compounds have attracted enormous attention from the chemical community. 6 In particular, the use of pyrazole-4,5-diones as a C-4 electrophile in asymmetric transformations, including the Friedel–Crafts reaction, 7 vinylogous aldol reaction, 8 [3 + 2] annulation reaction 9 and diorganozinc addition, 10 has recently been studied because of the easy access to pyrazolone derivatives bearing a quaternary stereocenter. In 2019, Wu's group 11 reported the first copper-catalyzed asymmetric alkynylation of pyrazole-4,5-diones with terminal alkynes in the presence of the cyclohexane-based amidophosphine ligand, and chiral propargylic alcohols bearing a pyrazolone motif could be obtained in excellent yields and enantioselectivities.…”
mentioning
confidence: 99%